Developmental programming and lineage branching of early human telencephalon. (24th September 2021) - Ma, Lin; Du, Yanhua; Hui, Yi; Li, Nan; Fan, Beibei; Zhang, Xiaojie; Li, Xiaocui; Hong, Wei; Wu, Zhiping; Zhang, Shuwei; Zhou, Shanshan; Xu, Xiangjie; et al.
Abstract: The dorsal and ventral human telencephalons contain different neuronal subtypes, including glutamatergic, GABAergic, and cholinergic neurons, and how these neurons are generated during early development is not well understood. Using scRNA‐seq and stringent validations, we reveal here a developmental roadmap for human telencephalic neurons. Both dorsal and ventral telencephalic radial glial cells (RGs) differentiate into neurons via dividing intermediate progenitor cells (IPCs_div) and early postmitotic neuroblasts (eNBs). The transcription factor ASCL1 plays a key role in promoting fate transition from RGs to IPCs_div in both regions. RGs from the regionalized neuroectoderm show heterogeneity, with restricted glutamatergic, GABAergic, and cholinergic differentiation potencies. During neurogenesis, IPCs_div gradually exit the cell cycle and branch into sister eNBs to generate distinct neuronal subtypes. Our findings highlight a general RGs‐IPCs_div‐eNBs developmental scheme for human telencephalic progenitors and support that the major neuronal fates of human telencephalon are predetermined during dorsoventral regionalization with neuronal diversity being further shaped during neurogenesis and neural circuit integration. Synopsis: Single‐cell RNA‐seq analysis of the developing human telencephalon provides a roadmap for the temporal generation of excitatory and inhibitory neurons. Radial glial cells progress into human telencephalic neurons via dividing intermediate progenitor cells and early postmitotic neuroblasts. The transcription factor ASCL1 plays an important role in the cell fate transition from radial glial cells to dividing intermediate progenitor cells in both dorsal and ventral telencephalic progenitors. Radial glial cells from the regionalized neuroectoderm are predetermined to differentiate into distinct neuronal identities. Dividing intermediate progenitor cells branch into sister early postmitotic neuroblasts to further shape neuronal diversity. Abstract : Single‐cell RNA‐seq analysis of the developing human telencephalon provides a roadmap for the generation of excitatory and inhibitory neurons.